The Relationship between Employability Skill and Job Mismatch towards Graduates’ Unemployment - Mohd Salahuddin, Nurin Farzana; Mahpar, Nurul Salizawatee; Ishak, Mohd Fikri (Information Management and Business Review, 2023)
Academic graduates are expected to contribute more significantly to industry and the national economy by bringing in skills, knowledge, innovation, and productivity. Their role is essential in driving industrial growth, sustainability, and overall development for economic growth. However, in Malaysia, the difficulty of finding employment for graduates has become a major problem, not only from the graduates’ point of view but also from the employer. While the graduates are struggling to find job openings that match their skills, the employers at the other end find it difficult to locate people who are compatible with their businesses’ vision. In Malaysia, several causes contributed to an increase in the unemployment rate for recent graduates including graduates’ lack of employability skills and job mismatches. Quality such as communication, soft skills, problem-solving, and creative abilities, are shown to be weak in unemployed graduates. This research attempts to examine the relationship between employability skills and job mismatches towards the graduate’s unemployment. A questionnaire has been developed to gather the data. Graduates of the Faculty of Business and Management (FBM), UiTM have been identified as the population. Descriptive and regression analyses were run using SPSS software. Findings suggested that both independent variables (employability skills and job mismatches) contributed significantly towards the graduate’s unemployment. This study is significant as it highlights the need for graduates to improve necessary skills such as leadership, communication, and interpersonal skills (Briones, G. et al., 2021) needed within the industry to land a job.